Critical Thinking in the Digital Age According to the Perspective of Hadith - Anadita Veria Sandi; Andi Nurlaela (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss critical thinking in the digital era according to the perspective of hadith. This research is a qualitative type by applying a literature study to interpret the hadith about critical thinking with a content analysis approach. The results and discussion of this study include the notion of critical thinking, hadith about critical thinking, and critical thinking in the digital era according to the perspective of hadith. This study concludes that in today's digital era, where science and technology is developing so rapidly, people must be objective in receiving information, so a critical attitude is needed. Critical thinking in Islam can be described by the concept of tabayyun. The concept of tabayyun has received special attention and has even been listed in the holy book of the Qur'an and hadith. This study recommends that further research be conducted on the hadith about critical thinking which has a correlation with the tabayyun concept.